La gamificación como herramienta para incentivar la comprensión lectora - Ruiz Bravo, Elizabeth Georgette; Falconí Narváez Rosa Magdalena (Machala : Universidad Técnica de Machala, 2022)
The present investigation destined to degree corresponds to the theme of gamification as a tool to encourage reading comprehension in third-year students of basic general education of the Rumiñahui school, destined from the identification of the problem that is located in the mentioned degree where students have some inconveniences when reading and understanding the text, it was also evidenced that teachers do not show a very broad knowledge about gamification, which causes classes to become monotonous and unmotivated. After that, the situation was evaluated and the objectives approach was presented, counting as a general objective to determine the influence of the use of gamification as a tool in the process of reading comprehension in third-year students A year of general education. basic of the Rumiñahui school during the period 2020-21. Establishing different actions that were going to impact and provide highly relevant information to support the investigation. Then the search for information was presented, organizing it properly after its selection, the theoretical argumentation of the two variables was managed on the one hand gamification and on the other reading comprehension, stratifying each subtopic to provide relevance to the study. Presenting a vision of conceptual frameworks, contextual in reference to the educational institution Rumiñahui, and legal according to regulations that support our research. After the theory presentation, the hypotheses corresponding to its verification were generated. Allocating the approach of the methodology, which corresponds to a quantitative-qualitative approach, under the use of descriptive methods for the arguments, experiment for the presentation of variables, and explanatory for evidencing their relationship and exposition of the results. Data collection techniques were used in conjunction with their respective instrument, such as survey and interview techniques, and the questionnaire. From the aforementioned, the data collection is presented through the instruments, then they are tabulated, analyzed and interpreted according to what is required. Within each analysis it is determined that the students understand a series of reading difficulties and that the teacher is unaware of their use. This is how, through a discussion of results, the presentation of the requirements is derived. And that is when the proposal is established, which was aimed at designing an instruction for parents and teachers, in order to publicize new platforms and develop reading comprehension skills for application in third-year EGB school students Rumiñahui. Presenting within this virtual document a series of steps and benefits that can be found when using the selected platform that was Primary World, each of the activities that can be found will seek to improve the reading comprehension of the students. In short, the presentation of the research comprises a series of steps that will carry out a comprehensive study, present results based on reality and managing a solution that meets the needs of the study subjects. Although it is true that reading is one of the most necessary actions for the academic world, it must be presented and trained under characteristics of excellence, and in the same way, the teacher's profile must be constantly updated for its most innovative praxis.
La presente investigación destinada a titulación corresponde a la temática la Gamificación como herramienta para incentivar la comprensión lectora en los estudiantes de tercer año de educación general básica de la escuela Rumiñahui, destinado a partir de la identificación de la problemática que se sitúa en el grado en mención donde los estudiantes presentan algunos inconvenientes al leer y entender el texto, además se evidenció que los docentes no muestran un conocimiento muy amplio sobre la Gamificación, lo que ocasiona que las clases se vuelvan monótonas y sin motivación. Posterior a eso se evaluó la situación y se presentó el planteamiento de objetivos, contando como objetivo general el determinar la influencia del uso de la gamificación como herramienta en el proceso de la comprensión lectora en los estudiantes de tercer año A año de educación general básica de la escuela Rumiñahui durante el periodo 2020-21. Estableciendo distintas acciones que iban a impactar y brindar información de gran relevancia para fundamentar la investigación. Luego se presentó la búsqueda de información, organizándola de manera adecuada luego de su selección, se gestionó la argumentación teórica de las dos variables por un lado gamificación y por otra comprensión lectora, estratificando cada subtema para aportar relevancia al estudio. Presentando una visión de marcos conceptuales, contextual en referencia a la institución educativa Rumiñahui, y legal según normativas que apoyan nuestra investigación. Luego de la presentación teoría, se generó las hipótesis correspondientes a su verificación. Destinando el abordaje de la metodología, la cual corresponde a un enfoque cuanticualitativo, bajo el uso de métodos descriptivos por las argumentaciones, experimentar por la presentación de variables, y explicativo por evidenciar su relación y exposición de los resultados. Se hizo uso de técnicas de recolección de datos en conjunto con su respectivo instrumento, como técnicas la encuesta y entrevista, y el cuestionario. A partir de lo antes mencionado, se va presentando la recopilación de datos por medio de los instrumentos, luego se los tabula, analiza e interpreta de acuerdo a lo requerido. Dentro de cada análisis se determina que los estudiantes comprenden una serie de dificultades de carácter lector y que el docente desconoce su uso. Es así como por medio de una discusión de resultados se deriva a la presentación de los requerimientos. Y es entonces cuando se establece a la propuesta, la cual fue orienta a diseñar un instructivo para padres y docentes, con el fin de dar a conocer nuevas plataformas y desarrollar habilidades de comprensión lectora para la aplicación en los estudiantes del tercer año de E.G.B escuela Rumiñahui. Presentando dentro de este documento de carácter virtual una serie de paso y beneficios que se pueden encontrar al uso la plataforma seleccionada que fue Mundo Primario, cada una de las actividades que se pueden encontrar pretenderán mejorar la comprensión lectora de los alumnos. En definitiva, la presentación de la investigación comprende una serie de pasos que efectuaran un estudio integral, presentan resultados en base a la realidad y gestionando una solución que se ajuste a las necesidades de los sujetos de estudio. Si bien es cierto la lectura es una de las acciones más necesarias para el mundo académico esta debe ser presentada y formada bajo características de excelencia, y de igual manera el perfil del docente estar en constantes actualizaciones para su praxis más innovadora.
Keywords: ENSEÑANZA; COMPRENSION LECTORA; GAMIFICACION; HERRAMIENTA DIGITAL